Community pharmacy intervention in managing sleep disorders: customers' belief and opinions - Mohamad Noor, Zaswiza; Smith, Alesha J. (Malaysian Pharmaceutical Society, 2015)
Pharmacists are in a suitable position to give advice and provide services related to sleep disorders to individuals who are unable to easily access sleep health centres. To improve the service, it is important to identify the customers’ point of views of the service and intervention. Study objectives are to: (1) identify opinions and beliefs of community pharmacy general services and sleep health interventions, and (2) investigate the possible reasons for attending a community pharmacy to seek help, amongst customers with sleep-related disorders. A set of self-administered questionnaires was completed by a convenience sample of customers who visited community pharmacies for sleep-related disorders. Results showed that four most influential reasons affecting customers’ decisions to attend a community pharmacy to seek help for sleep-related disorders were satisfaction with the previous services received from the pharmacy (95.1%), easily accessible premise (95.1%), belief that pharmacist always treat them with courtesy and respect (93.6%), and belief that pharmacist often show concern for customers (90.3%). Gender (female) and a higher education level are two main characteristics that influence decisions. Opinions of community pharmacy do not appear to differ between those with more or less severe sleep disorders. Hence, it can be concluded that there are a variety of reasons affecting customers’ decisions to attend a community pharmacy. However, these do not appear to be related to the level of risks of sleep disorders. Those who seek help to improve sleep-related disorders from a community pharmacy have high opinions of the pharmacist’s attitudes toward customers.